GAME EDUKASI DIGITAL ULAR TANGGA BERMUATAN ETNOMATEMATIKA DI SEKOLAH DASAR - Suriyana Suriyana; Nizarrahmadi Nizarrahmadi (JURNAL PENDIDIKAN DASAR, 2022)
Abstract: This research aims to create a digital educational game based on ethnomathematics in Snakes and Ladders game. This research was conducted at the 51 Sungai Raya State Elementary School, Kubu Raya Regency. The method in this research was the development of method of 4-D (Four D Model). Based on the results of the validity test that is conducted by 2 experts, it shows a valid level of validity with an average of 3.8 with details of material experts with a score of 3.9 while media experts score an average value of 3.7 with valid criteria. As for the effectiveness of the results of student responses, 3.52 states that students agree with learning mathematics, especially integer operations, while the evaluation of the results of the overall percentage of students who complete is 86% in elementary schools practical to use. Keywords: Snakes and Ladders Educational Game, Ethnomathematics. Abstrak: Penelitian ini bertujuan untuk membuat game edukasi digital berbasis etnomatematika dalam permainan Ular Tangga. Penelitian ini dilaksanakan di Sekolah Dasar Negeri 51 Sungai Raya Kabupaten Kubu Raya. Metode yang digunakan dalam penelitian ini adalah metode pengembangan dengan 4- D (Four D Model). Berdasarkan hasil uji validitas yang dilakukan oleh 2 ahli, menunjukan tingkat kevalidan yang valid dengan rerata 3,8 dengan rincian ahli materi dengan skor nilai 3.9 sedangkan ahli media skor nilai rata rata 3.7 dengan kriteria valid. Sedangkan untuk ke efektivitas hasil dari respon siswa bahwa 3.52 denagn menyatkan bahwa siswa setuju dengan pembelajaran matematika khusunya operasi bilnagan bulat, sedangkan evaluasi hasil keseluruhan persentase siswa yang tuntas adalah 86% di Sekolah Dasar praktis untuk digunakan Kata Kunci: Game Edukasi Ular Tangga, Etnomatematika.